Redesign and modernisation of an NHS cataract service (Fife 1997-2004): multifaceted approach. Issue 7585 (18th January 2007) - Tey, Adrian; Grant, Barbara; Harbison, Dawn; Sutherland, Shona; Kearns, Patrick; Sanders, Roshini
Abstract : Problem A Scottish national health service ophthalmic facility was unable to cope with increasing demand for cataract surgery. Design Multifaceted approach to redesign hospital space to accommodate a cataract unit; to invest in cataract nursing staff to allow more operations under local anaesthesia and as day cases; and to enhance input by general practitioners and optometrists to streamline and reduce false positive cataract referrals. A prospective audit for productivity was undertaken in 2004 (two years after the redesign) and compared against the national cataract surgery audit data for Fife from 1997. Setting District general hospital serving a population of 400 000 in south east Scotland. Key measures for improvement Increasing throughput of cataract surgery while assessing quality of care provided against predefined evidence and Royal College of Ophthalmologists' guidelines, and evaluating training standards for ophthalmic surgical trainees against higher surgical training requirements. Strategies for change Cataract services were redesigned to increase throughput and to reduce waiting times while preserving the quality of patient care. A secondary end point was to maintain surgical case load mix thus allowing trainees to continue to fulfil the number of operations required to acquire higher surgical training standards. Effects of change In the same three month period 237 cataract operations were carried out in 1997 and 374 in 2004, representing an increase of productivity by 60%. The waiting time for surgery decreased from more than one year to three months. The redesign resulted in almost complete preoperative and postoperative assessment by nursing staff, thus freeing medical time and allowing for more operations. Optometrists' referrals with reports increased significantly (P<0.0001). The number of operations carried out as day cases under local anaesthesia increased, with fewer intraoperative complications and postoperative visits (P<0.0001). The number of operations carried out by trainees more than doubled, from 43 to 100 cases, thus improving training opportunities. Lessons learnt Modest capital investment in rebuilding space and in staff for cataract services can improve the quality and volume of cataract surgery. Enhancing existing NHS services provides for future need while maintaining training standards, thus potentially obviating the need for independent treatment centres. This model could be used throughout the United Kingdom.